2006
DOI: 10.1128/aem.72.2.1613-1622.2006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Regulated Formation of Mycelial Mat-Like Biofilms by Legionella pneumophila

Abstract: Fifty strains representing 38 species of the genus Legionella were examined for biofilm formation on glass, polystyrene, and polypropylene surfaces in static cultures at 25°C, 37°C, and 42°C. Strains of Legionella pneumophila, the most common causative agent of Legionnaires' disease, were found to have the highest ability to form biofilms among the test strains. The quantity, rate of formation, and adherence stability of L. pneumophila biofilms showed considerable dependence on both temperature and surface mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 65 publications
6
101
1
3
Order By: Relevance
“…Our study has revealed that biofilm formed by L. pneumophila is more consistent at 20 u C than at 37 or 42 u C. Piao et al (2006) also reported that the L. pneumophila biofilms with structural features typical of biofilms (i.e. pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our study has revealed that biofilm formed by L. pneumophila is more consistent at 20 u C than at 37 or 42 u C. Piao et al (2006) also reported that the L. pneumophila biofilms with structural features typical of biofilms (i.e. pillar-and mushroom-like structures) formed at 25 u C remained more stably attached than filamentous, mycelial-mat-like biofilms formed at 37 and 42 u C. Also, Mampel et al (2006) reported that biofilm formation at 37 u C was 30 % lower than at 23 and 30 u C. Furthermore, we have shown that adhesion is highest for late stationary phase cells.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, two different studies have investigated the ability of L. pneumophila to form monospecies biofilms. Piao et al (2006) tested different materials and temperatures for biofilm formation, reporting that on glass and polystyrene biofilms were formed more slowly at 25 u C than at 37 or 42 u C but that they remained more stably attached at 25 u C. At 25 u C biofilms possessed structural features typical of biofilms reported previously (i.e. pillar-and mushroom-like structures) whereas at 37 u C, filamentous, mycelial-mat-like biofilms were the structures observed.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Temperature is an important factor for biofilm formation, and numerous studies have indicated that temperature affects the amount of biofilm in Escherichia coli, Legionella pneumophila, Listeria monocytogenes, and B. cereus (41)(42)(43)(44). In C. perfringens, temperature drastically affects biofilm morphology, potentially reflecting the temperature-dependent regulation of EPS production and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Relatos encontrados na literatura consultada sugerem associação entre a presença de biofilme e a presença do gênero Legionella. [20][21][22] No presente estudo, entretanto, não foi possível demonstrar essa relação dado o número de amostras positivas para a presença de Legionella sp. e a grande variação na concentração de bactérias heterotróficas nas amostras analisadas.…”
Section: Discussionunclassified